Rethinking the legal definitions of cultural heritage from gender and decolonial point of view - Ivana Nikolić; Miljana Jakovljevic (Huarte de San Juan. Geografía e Historia)
Protection of cultural heritage is vital for survival of cultural identity, collective memory and preserving deeply integrated values. Prerequisite for this achievement is a well drafted definition of cultural heritage in international legal framework. Yet, adopted legal instruments have faced multiple criticism coming from legal doctrine, practicing lawyers and even bearers of the heritage. There are a couple of definitions. Heritage is divided, even though tangible and intangible heritage are considered to be «two sides of the same coin». Some of the definitions are descriptive, restrictive, too wide, too narrow, problematic to interpret, etc. Moreover, lack of inclusivity makes them easily challenged from gender and decolonial point of view. Consequences of patriarchal and Eurocentric approach are reflecting on the heritage, but also on the limitation of human rights of the bearers. Overall, questioning existing legal acts and implemented system is necessary in order to safeguard heritage for future generations.